Management of Equipment and Machinery Assets Owned by Regional Government - Mediaty, M.; Muhaimin, M.; Asriani , A.; Nursehan, N.; Kaharuddin, K. (Golden Ratio of Finance Management, 2024)
This research aims to analyze the management of equipment and machine assets belonging to local governments. This research is categorized as descriptive research, which seeks an overview and explanation of leadership strategies regarding effectiveness, performance, etc. The data is collected in report excerpts and not in numbers that provide an overview of the presentation and secondary data, namely data and information quoted from books, journals, print media, and articles related to regional asset management. Data collection was carried out through observation, interviews, and documentation. The results obtained by the West Sulawesi Provincial Government in OPD X have implemented asset management of its equipment and machinery. However, there are obstacles to its implementation. The West Sulawesi Provincial government at OPD carries out the inventory stage. Furthermore, it is still at the equipment and machine asset inventory stage, and the West Sulawesi Provincial government has not codified and labeled every equipment and machine asset it owns.